2014
DOI: 10.1007/s13277-014-1705-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine triggers apoptosis by regulating Bcl-2 family proteins and activating caspase-3/caspase-9 pathway in human leukemia HL-60 cells

Abstract: With the objective of identifying promising antitumor agents for human leukemia, we carried out to determine the anticancer ability of oxymatrine on the human leukemia HL-60 cell line. In vitro experiments demonstrated that oxymatrine reduced the proliferation of HL-60 cells in a dose- and time-dependent manner via the induction of apoptosis and cell cycle arrest at G2/M and S phases. The proteins involved in oxymatrine-induced apoptosis in HL-60 cells were also examined using Western blot. The increase in apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…6,[21][22][23] However, little is known about its effects on human hepatoma, and the precise mechanism involved remains largely unknown. Therefore, in this study, we proved the anticancer effects of oxymatrine on human hepatoma Hep-G2 and SMMC-7721 cells and explored the related molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,[21][22][23] However, little is known about its effects on human hepatoma, and the precise mechanism involved remains largely unknown. Therefore, in this study, we proved the anticancer effects of oxymatrine on human hepatoma Hep-G2 and SMMC-7721 cells and explored the related molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…During the process, apoptosis is characterized by cell shrinkage, chromatin condensation, blebbing of the plasma membrane, and nuclear condensation without cell lysis. 21,24 Apoptosis can be induced by a variety of physical and chemical factors and drugs. 25 Since deregulation of apoptosis is the hallmark of all cancer cells, 26 the induction of apoptosis has been described as a standard and best strategy in anticancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it has become an urgent need to find a low toxicity and efficient plant extract medicine applied to the cancer treatment. Nowadays, growing evidences suggest that natural materials might be a good vehicle to anticancer [2,3]. Due to these extracts showed low toxicity and high biological activities, a lot of herb products have been used in alternative treatments of cancers [4].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, anti-apoptotic agents that mitigate neurodegeneration caused by apoptosis are known to prevent the spread of neuronal diseases [41e43]. Therefore, to establish a dynamic system to study the cellular population, we generated a FRET bioprobe for caspase-9, an upstream mediator of caspase-3 activity during apoptosis; the signal transduction properties of caspase-9 were compared with those of caspase-3 [44,45]. In this study, we also demonstrated the feasibility and future applicability of the FRET bioprobe in an apoptotic protease inhibitor/activator screening assay.…”
mentioning
confidence: 99%